11.6=x/3+13

Simple and best practice solution for 11.6=x/3+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11.6=x/3+13 equation:



11.6=x/3+13
We move all terms to the left:
11.6-(x/3+13)=0
We get rid of parentheses
-x/3-13+11.6=0
We multiply all the terms by the denominator
-x-13*3+(11.6)*3=0
We add all the numbers together, and all the variables
-1x-4.2=0
We move all terms containing x to the left, all other terms to the right
-x=4.2
x=4.2/-1
x=-4+0.2/1

See similar equations:

| -3(4x-10)+12=-12x+42 | | 39-7n=20+12n | | 40n+70=30n+90 | | 11h+3h+h−12h+4h=14 | | 6x^2+12x+9=5 | | 15x-12=102 | | 12+2x=18x+x | | X+4=13x= | | 9=4r+1 | | 17=4y+1 | | 5y+68=91 | | -3|x|=-9 | | x+.12x=550 | | x³-221,751*x-15625=0 | | 15=3w+3 | | 60+45=5x+8x | | 12y+12+8=9(y-1)+26 | | 10x+11=99 | | 4x+8=3(x-5) | | -3y/12=9 | | (x+10)(x+14)=(x-14)(x-20) | | 5/8=x/80 | | 6x+4^4=6x+2 | | H(x)=x^2+3x-2 | | H(x)=x^2+3x-2; | | 4y+24=96 | | 15x-6x=(-x+3)-(x+2)+10 | | 2(1/4)x+3=4(1/8) | | 2(1/4)m+3=4(1/8) | | 6(2x=4)=4(3x+6) | | 12n×6=-6n | | 5(3+2)=7x |

Equations solver categories